(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
This research aims to present the Murabaha standard and the accounting treatments for it as stated in the standards of the AAOIFI Authority, which is an international body, and one of its most important activities is the compliance of standards for Islamic banking work. These standards have become respected, trusted and committed by most Islamic banks around the world. As well as the presentation of the actual application of Murabaha as applied by the Islamic Bank of Iraq, which is the largest and oldest Islamic bank in Iraq